x+15+x+15+x+x=x+45+x+40+x+25

Simple and best practice solution for x+15+x+15+x+x=x+45+x+40+x+25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+15+x+15+x+x=x+45+x+40+x+25 equation:


Simplifying
x + 15 + x + 15 + x + x = x + 45 + x + 40 + x + 25

Reorder the terms:
15 + 15 + x + x + x + x = x + 45 + x + 40 + x + 25

Combine like terms: 15 + 15 = 30
30 + x + x + x + x = x + 45 + x + 40 + x + 25

Combine like terms: x + x = 2x
30 + 2x + x + x = x + 45 + x + 40 + x + 25

Combine like terms: 2x + x = 3x
30 + 3x + x = x + 45 + x + 40 + x + 25

Combine like terms: 3x + x = 4x
30 + 4x = x + 45 + x + 40 + x + 25

Reorder the terms:
30 + 4x = 45 + 40 + 25 + x + x + x

Combine like terms: 45 + 40 = 85
30 + 4x = 85 + 25 + x + x + x

Combine like terms: 85 + 25 = 110
30 + 4x = 110 + x + x + x

Combine like terms: x + x = 2x
30 + 4x = 110 + 2x + x

Combine like terms: 2x + x = 3x
30 + 4x = 110 + 3x

Solving
30 + 4x = 110 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
30 + 4x + -3x = 110 + 3x + -3x

Combine like terms: 4x + -3x = 1x
30 + 1x = 110 + 3x + -3x

Combine like terms: 3x + -3x = 0
30 + 1x = 110 + 0
30 + 1x = 110

Add '-30' to each side of the equation.
30 + -30 + 1x = 110 + -30

Combine like terms: 30 + -30 = 0
0 + 1x = 110 + -30
1x = 110 + -30

Combine like terms: 110 + -30 = 80
1x = 80

Divide each side by '1'.
x = 80

Simplifying
x = 80

See similar equations:

| 7/6*x/42 | | 7x+35=2x+140 | | (-28x^12y^5)^1/2 | | 0=(x-2) | | -6y+18=-24 | | 42/7*x/6 | | j(x+yj)+2(x-yjh)+1-j=0 | | 16z=48 | | -30-(-51)=x/8 | | x-53=15 | | 4(2c+4)=48 | | y^4-2y+y=0 | | 62.34=k-10.7 | | 4x(2c+4)=48 | | 2x+3y=0.67 | | 2m-2s-1=1 | | x/x-12=4 | | 2n-6=8(8n+6)+8 | | jz+2z+1-j=0 | | x+43=119 | | -.5(32)*x^2+16x=2.56 | | 9+3(z-3)=-5z+5 | | 3-8(1+9z)=15 | | .5(32)*x^2+16x=2.56 | | 72/6x | | g(x)=-(2/3)^x= | | -7(n+4)+31=-4n-12 | | -6(x-3)=-12 | | 4/15x-5 | | 5t=32 | | 44-19=5(x-4) | | 12u+2u-7u-6u=4 |

Equations solver categories